Penerapan Budaya Pijat Bayi Sebagai Terapi Komplenter Untuk Meningkatkan Kualitas Tidur Sebagai Upaya Pencegahan Stunting Pada Bayi - Wibowo, Daniel Akbar; Zen, Dini Nurbaeti; Dewi, Wildan Sofia (Kolaborasi: Jurnal Pengabdian Masyarakat, 2024)
Background: One of the main factors for babies to get quality sleep is with complementary massage. Baby massage is a touch therapy that can provide a sense of security and comfort to babies. Massage can help reduce muscle tension, so that the benefits obtained are that babies become calmer, more relaxed and sleep better (Permata, 2017). The aim is to determine whether there is an influence of massage culture as a complementary therapy on the quality of Baby Sleep (aged 1-12 months) in an effort to prevent stunting in Gunung Cupu Village, Ciamis Regency. Method: This study is a Quasi-experimental study with a One Group PreTest PostTest Design research design approach. Sample: The target of this study was babies (aged 1-12 months) in the Gunung Cupu Village area, Ciamis Regency, the sampling technique used consecutive sampling, namely selection by determining subjects who met the research criteria would be included in the study until a certain time until the number of samples was met and the data analysis technique in this study used Mann-Whitney. Results: Description of Baby Sleep Quality before Massage Therapy was given to Babies (1-12 months) in Gunung Cupu Village, Ciamis Regency, namely a small portion of respondents 3 people were good (30%), almost half of them 4 people were sufficient (40%), and most of the respondents 3 people (30%), description of Baby sleep quality after Massage Therapy was given to Babies (1-12 months) in Gunung Cupu Village, Ciamis Regency, namely almost half of them 4 people were Good (40%), most of the respondents 6 people were Sufficient (60%), and none of the respondents 0 people were Less (0%), there was an effect of Massage Therapy on Baby Sleep Quality (1-12 months) in Gunung Cupu Village, Ciamis Regency, analyzed using the Wilcoxon test with the results of the value of ρ (0.04) <α (0.05).